Regulation of the molecular repertoires of oxidative stress response in the gills and olfactory organ of Atlantic salmon following infection and treatment of the parasite Neoparameoba perurans. Issue 130 (November 2022) - Furtado, Francisco; Breiland, Mette W.; Strand, David; Timmerhaus, Gerrit; Carletto, Danilo; Pedersen, Lars-Flemming; Afonso, Fernando; Lazado, Carlo C.
Abstract: The present study investigated the involvement of key molecular regulators of oxidative stress in amoebic gill disease (AGD), a parasitic infestation in Atlantic salmon. In addition, the study evaluated how these molecular biomarkers responded when AGD-affected fish were exposed to a candidate chemotherapeutic peracetic acid (PAA). Atlantic salmon were experimentally infected with the parasite Neoparameoba perurans, the causative agent of AGD, by bath exposure and after 2 weeks, the fish were treated with three commercial PAA products (i.e., Perfectoxid, AquaDes and ADDIAqua) at a dose of 5 ppm. Two exposure durations were evaluated – 30 min and 60 min. Sampling was performed 24 h and 2 weeks after PAA treatment (equivalent to 2- and 4-weeks post infection). At each sampling point, the following parameters were evaluated: gross gill pathology, gill parasitic load, plasma reactive oxygen species (ROS) and total antioxidant capacity (TAC), histopathology and gene expression profiling of genes with key involvement in oxidative stress in the gills and olfactory organ. AGD did not result in systemic oxidative stress as ROS and TAC levels remained unchanged. There were no clear patterns of AGD-mediated regulation of the oxidative stress biomarkers in both the gills and olfactory organ; significant changes in the expression were mostly related to time rather than infection status. However, the expression profiles of the oxidative stress biomarkers in AGD-affected salmon, following treatment with PAA, revealed that gills and olfactory organ responded differently – upregulation was prominent in the gills while downregulation was more frequent in the olfactory organ. The expression of catalase, glutathione S-transferase and thioredoxin reductase 2 was significantly affected by the treatments, both in the gills and olfactory organ, and these alterations were influenced by the duration of exposure and PAA product type. Parasitic load in the gills did significantly increase after treatment regardless of the product and exposure duration; the parasite was undetectable in some fish treated with AquaDes for 30 mins. However, PAA treated groups for 30 min showed lower macroscopic gill scores than the infected-untreated fish. Histology disclosed the classic pathological findings such as multifocal hyperplasia and increased number of mucous cells in AGD-affected fish. Microscopic scoring of gill injuries showed that AGD-infected-PAA-treated fish had lower scores, however, an overall trend could not be established. The morphology and structural integrity of the olfactory organ were not significantly altered by parasitism or PAA treatment. Collectively, the results indicate that AGD did not affect the systemic and mucosal oxidative status of Atlantic salmon. However, such a striking profile was changed when AGD-affected fish were exposed to oxidative chemotherapeutics. Moreover, the gills and olfactory organ demonstrated distinct patterns of gene expression of oxidative stress biomarkers in AGD-infected-PAA-treated fish. Lastly, PAA treatment did not fully resolve the infection, but appeared not to worsen the mucosal health either. Highlights: AGD did not result in systemic oxidative stress as ROS and TAC levels remained unchanged. No clear patterns of AGD-mediated regulation of the oxidative stress biomarkers in both the gills and olfactory organs. Exposure to oxidant altered the oxidative stress genes in the gills and olfactory organs of AGD-affected salmon. Upregulation was prominent in the gills while downregulation was more frequent in the olfactory organs. PAA treatment did not fully resolve the infection, but appeared not to worsen the mucosal health either.